2019
DOI: 10.1177/1098612x19880434
|View full text |Cite
|
Sign up to set email alerts
|

Feline abdominal ultrasonography: What’s normal? What’s abnormal? The diseased gastrointestinal tract

Abstract: Practical relevance: Abdominal ultrasound plays a vital role in the diagnostic work-up of many cats presenting to general and specialist practitioners. B-mode ultrasonography is likely the most widely used modality for imaging the gastrointestinal (GI) tract in cats and it can help in the diagnosis of GI masses, foreign bodies and disorders of the ileocaecocolic junction. Clinical challenges: Despite ultrasonography being a commonly used modality, many practitioners are not comfortable performing an ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 97 publications
(237 reference statements)
1
11
1
Order By: Relevance
“…Concerning B-mode qualitative values, there were no statistically significant differences in terms of layer definition, localization, and echogenicity between these three groups, but only if compared to HGAL. These results agree with the literature for US findings in inflammatory and neoplastic disease of the small intestine both in dogs and cats [ 5 , 8 , 9 , 11 , 12 , 38 , 43 , 44 ]. These results indicate that, even for gastric involvement, inflammatory and low-grade lymphomatous infiltrates have similar US features, which are indistinguishable without an adequate histological or immunohistochemical characterization.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning B-mode qualitative values, there were no statistically significant differences in terms of layer definition, localization, and echogenicity between these three groups, but only if compared to HGAL. These results agree with the literature for US findings in inflammatory and neoplastic disease of the small intestine both in dogs and cats [ 5 , 8 , 9 , 11 , 12 , 38 , 43 , 44 ]. These results indicate that, even for gastric involvement, inflammatory and low-grade lymphomatous infiltrates have similar US features, which are indistinguishable without an adequate histological or immunohistochemical characterization.…”
Section: Discussionsupporting
confidence: 93%
“…Lymphoma is the most common GI-related malignancy in the cat, representing 30% of all feline neoplasms; moreover, 70% of cats with lymphoma have GI involvement: In this species, the small intestine is the most commonly affected site and is also the most frequent tumour of the gastric wall (Willard, 2012;Paulin et al, 2018). The Siamese breed and the older age (between 10 and 14 years in particular) are correlated to an increased risk (Griffin, 2019). Lymphoma is less common in dogs than in cats; furthermore, Alimentary Lymphoma (AL) represents only 7% of all canine lymphoma (Gieger, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With primary gastrointestinal disease, ultrasonographic changes commonly include changes in the thickness of the wall and potentially loss of layering. Loss of layering of the GI tract is most commonly associated with neoplasia; however, it can occasionally be seen in cats with severe inflammatory disease (Griffin 2019c).…”
Section: Abdominal Imagingmentioning
confidence: 99%
“…Lymphoma can present as solitary or multiple intestinal masses (these are most often transmural, hypoechoic, circumferential thickenings of the GI wall, associated with loss of normal wall layering), or as a diffuse thickening of the small intestinal muscularis layer with otherwise normal wall layering (Griffin 2019c). A previous study has identified a significant increased thickness of the intestinal wall and muscularis propria layer in the small intestines of cats with GI small cell T‐cell lymphoma and IBD.…”
Section: Abdominal Imagingmentioning
confidence: 99%